Constructing and Negotiating Chinese Cultural Identity in Diaspora Through Music and Martial Arts - McGuire, Colin (Intersections, 2018)
The Hong Luck Kung Fu Club has been a fixture of Toronto’s Chinatown for over fifty years. Its curriculum includes not only self-defence skills, but also percussion music for accompanying martial arts demonstrations and lion dancing. Hong Luck’s blurred genre is a tool for preserving, transmitting, and promoting culture. At the same time, practitioners negotiate their identities in diverse ways. I thus interpret kung fu as a flexible, embodied practice whose purview extends beyond physical combat. Based on fieldwork at Hong Luck, this article uses cognitive semantics and phenomenology to demonstrate that kung fu, lion dance, and percussion help (re)construct Chinese identities emergently and strategically.